Brick in the wall? Linking quality of debriefing to participant learning in team training of interprofessional students. (27th January 2021) - Paige, John T; Garbee, Deborah D; Yu, Qingzhao; Zahmjahn, John; Baroni de Carvalho, Raquel; Zhu, Lin; Rusnak, Vadym; Kiselov, Vladimir J
Abstract : Background: The evidence for the conventional wisdom that debriefing quality determines the effectiveness of learning in simulation-based training is lacking. We investigated whether the quality of debriefing in using simulation-based training in team training correlated with the degree of learning of participants. Methods: Forty-two teams of medical and undergraduate nursing students participated in simulation-based training sessions using a two-scenario format with after-action debriefing. Observers rated team performance with an 11-item Teamwork Assessment Scales (TAS) instrument (three subscales, team-based behaviours (5-items), shared mental model (3-items), adaptive communication and response (3-items)). Two independent, blinded raters evaluated video-recorded facilitator team prebriefs and debriefs using the Objective Structured Assessment of Debriefing (OSAD) 8-item tool. Descriptive statistics were calculated, t-test comparisons made and multiple linear regression and univariate analysis used to compare OSAD item scores and changes in TAS scores. Results: Statistically significant improvements in all three TAS subscales occurred from scenario 1 to 2. Seven faculty teams taught learners with all scores ≥3.0 (except two) for prebriefs and all scores ≥ 3.5 (except one) for debriefs (OSAD rating 1=done poorly to 5=done well). Linear regression analysis revealed a single statistically significant correlation between debrief engagement and adaptive communication and response score without significance on univariate analysis. Conclusions: Quality of debriefing does not seem to increase the degree of learning in interprofessional education using simulation-based training of prelicensure student teams. Such a finding may be due to the relatively high quality of the prebrief and debrief of the faculty teams involved in the training.